Enhanced power generation, faster transient response and longer durability of HT-PEMFC using composite polybenzimidazole electrolyte membrane with optimum rGO loading. (24th June 2020) - Ghosh, Priyanka; Mandal, Sayantanu; Majumdar, Sayani; Sarkar, Arundhati; Ganguly, Saibal; Kargupta, Kajari
Abstract: Here we report enhanced power generation, faster transient response and longer durability of HT-PEMFC by employing a composite membrane of PBI with reduced graphene oxide (rGO) at an optimum loading of 1%. Easy and low cost synthesis of the composite membranes at different loading of rGO is achieved using methane sulfonic acid (MSA) as solvent that resolves the long-standing issue of poor solubility of PBI in the conventional solvents. Property and performance mapping with respect to rGO loading not only leads to attain the optimum but also identifies the window of feasible operating zone. It is observed that with very low (1%) rGO content, composite PBI membrane (rGO-PBI-1) offers the maximum enhancement of all properties viz water uptake, acid uptake, proton conductivity, ion exchange capacity, acid retention capacity, chemical stability, yield strength, while beyond a threshold/critical loading ( 4%) deterioration of electrochemical and mechanical properties occur. Steady state performance analysis reveals almost two times peak power enhancement of HT-PEMFC using rGO-PBI-1 electrolyte membrane at an operating temperature of 170 °C; insitu impedance analysis during fuel cell operation reveals sharp decay in charge transfer resistance. Multiple step response analysis confirms ( 2 times) faster transient response of fuel cell using rGO-PBI-1 while compared to that with pristine PBI membrane. Fuel cell stability analysis ensures longer durability of operation with negligible decay in voltage. Graphical abstract: Image 1 Highlights: Low cost easy synthesis of rGO-PBI composite electrolyte using MSA as solvent. Optimum (1%) and critical (4%) rGO loading from property-performance mapping. 2 times power generation at 170 °C using optimum rGO loading. Enhancement of proton conductivity from Insitu Impedance analysis. Faster transient step response of fuel cell using 1% rGO.